Exploring factors affecting psychological resilience of farmers living in drought-affected regions in Iran: a qualitative study - Tahernejad, Azadeh; Sohrabizadeh, Sanaz; Mashhadi, Ali (Frontiers in Psychology, 2024)
Introduction Drought, a prevalent consequence of climate change, significantly impacts mental health among farmers. Enhancing psychological resilience is crucial to mitigating these effects. This study aims to explore the concept and factors affecting the psychological resilience of farmers living in drought-affected regions in Iran. Method This study utilized a conventional qualitative content analysis method. Twenty-six participants, divided into two groups of experts and farmers, were selected through purposive sampling. Data collection was conducted via in-depth semi-structured interviews. The study adhered to the Consolidated Criteria for Reporting Qualitative Research (COREQ) checklist and was carried out between June 2023 and February 2024. Results The factors affecting the psychological resilience of farmers living in drought-affected regions were categorized into two main categories with nine subcategories. The first category, environmental factors, included economic factors, socio-cultural factors, drought adaptation methods, government policies, and infrastructural factors. The second category, intra-individual factors, comprised personal characteristics, health factors, psychological factors, and perception and knowledge. Conclusion The study revealed that both environmental and intra-individual factors influence the psychological resilience of farmers during droughts. It is recommended to implement intervention strategies, such as providing training and education on drought adaptation methods and managing agricultural and healthcare expenses. Further research is needed to expand this concept to various disasters and occupational groups in future studies.